THE ISSUE OF FAITH (IMAN) IN THE WORK TA’WILAT AL-QUR’AN (The Journal of Interdisciplinary Human Studies, 2025)
This article is devoted to the views on the issues of faith expressed in Abu Mansur Moturidi’s work “Ta’wilot al-Qur’an”. It is known that Abu Mansur Moturidi lived and created at the time when the distortions in the belief were at their peak, and at the same time he refuted several erroneous categories such as khawarij, mu’tazilites, and karromites with both intellectual and narrative evidence. In this work of Moturidi, not only in his time, but also in today’s time, there are enough refutations of currents that try to achieve their selfish goals by throwing various conflicting issues among the civilians who are living harmoniously and by distracting them.
Keywords: tafsir; aqeedah; faith; kufr; discord, khawarij; mu’tazilites; karromites